2002
DOI: 10.1023/a:1015566312032
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A galactomannan (GMPOLY) isolated from lichen Ramalina celastri was complexed with vanadyl ion (IV;VO) forming the complex GMPOLY-VO. Both GMPOLY and GMPOLY-VO diminished the superoxide anion production by macrophages triggered with PMA, the complex giving rise to this effect at concentrations 100 times lower than GMPOLY. Macrophages treated with GMPOLY enhanced the nitric oxide production (40%), this effect not being observed when interferon-gamma (IFN-gamma) or IFN-gamma plus lipopolysaccharide (LPS) were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…2). Noleto [17] suggested that the increase in 40% on NO production was responsible for the leishmanicidal effects of GMPOLY. Ghosh [6] showed that the production of NO from macrophages treated with the antileishmanial drugs in the current use is necessary to their leishmanicidal activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). Noleto [17] suggested that the increase in 40% on NO production was responsible for the leishmanicidal effects of GMPOLY. Ghosh [6] showed that the production of NO from macrophages treated with the antileishmanial drugs in the current use is necessary to their leishmanicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide activity on intracellular amastigotes was measured as described by [17]. Peritoneal macrophages were plated in 24-well plates (5 × 10 5 cells/well) and left to adhere for 2 h. Non-adherent cells were removed and macrophages were infected with promastigotes (5 parasites per macrophage), followed by 12 h of incubation at 34 • C in the presence of 5% CO 2 .…”
Section: Measurement Of Intracellular Parasite Killingmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Complexation occurred with Me 6Me-a-Galp and Me 2,6-Me 2 -a-Galp, which have 3,4-cis-diols, but not with Me 3Me-b-Galp, which contains free 4,6-OH groups. 8 As an aqueous solution of a complex of oxovanadium(IV) with a lichen galactomannan gave rise to activities related to peritoneal macrophages and leishmanicidal activity, 9 we now examine the formation of esters of selected polysaccharides with NaVO 3 without accompanying buffer, which could be biologically prejudicial. Tested were galactopyranose, mannopyranose-, and mannopyranoseuronic acid-containing polysaccharides, taking into account a surprising preliminary experiment, in which 51 V NMR spectroscopy showed an almost complete lack of complexation with methyl b-mannopyranoside (Table 1).…”
mentioning
confidence: 99%